Health risk appraisal in older people 7: long-acting benzodiazepine use in community-dwelling older adults in London: is it related to physical or psychological factors?. Issue 3 (22nd February 2017) - Chatterjee, Devoshree; Iliffe, Steve; Kharicha, Kalpa; Harari, Danielle; Swift, Cameron; Gillman, Gerhard; Stuck, Andreas E.
Abstract : Aim: To investigate whether the use of long-acting benzodiazepines, in individuals aged 65 and over is mediated by physical or psychological factors. Background: Long-acting benzodiazepine consumption among older people has implications for mortality, morbidity and cost-effective prescribing. Two models explain benzodiazepine use in this age group, one linked to physical illness and disability and one to psychological factors. Methods: Secondary analysis of baseline data from a study of 1059 community-dwelling non-disabled people aged 65 years and over recruited from three general practices in London. For this analysis, use of long-acting benzodiazepines was defined as any self-reported use of diazepam or nitrazepam in the last four weeks. Associations between demographic factors, health service use, and physical and psychological characteristics and benzodiazepine use were investigated. Findings: The prevalence of benzodiazepine use in this sample was 3.3% (35/1059). In univariate analyses, benzodiazepine use was associated with female gender, low income, high consultation rates, physical factors (medication for arthritis or joint pain, polypharmacy, difficulties in instrumental activities of daily living, recent pain) and psychological factors (poor self-perceived health, social isolation, and symptoms of anxiety or agitation). In a multivariate logistic regression analysis only two factors retained statistically significant independent associations with benzodiazepine use: receiving only the state pension (OR=4.0, 95% CI: 1.70, 9.80) and pain in the past four weeks (OR=3.79, 95% CI: 1.36, 10.54).